Bone wax reduces blood loss after total hip arthroplasty: a prospective, randomized controlled study - Li, Hao; Huang, Chao; Ding, Zi-Chuan; Liu, Zun-Han; Zhao, En-Ze; Zhou, Zong-Ke (Frontiers in Medicine, 2023)
Background: Previous studies have demonstrated the efficacy of bone wax in reducing blood loss in various orthopaedic surgeries. However, the effect of bone wax on total hip arthroplasty (THA) remains unclear. The objective of this study was to assess the efficacy of bone wax in THA. Methods: We enrolled 104 patients in this randomized controlled trial. These patients were randomized (1:1) to either the bone wax or control group. The primary outcome was total blood loss after THA. The secondary outcomes included serum haemoglobin (Hb) level, change in Hb level, lower limb diameters on the first and third postoperative day (POD), range of motionat discharge, length of postoperative hospital stay, and adverse events. Results: Patients in the bone wax group had significantly lower total blood loss on PODs 1 and 3 (p < 0.05). Moreover, patients in the bone wax group performed better in terms of postoperative serum Hb level, change in Hb level on PODs 1 and 3, and length of postoperative hospital stay (all p < 0.05). Patients in the bone wax group did not experience any bone wax-related adverse events. Conclusions: Bone wax administration in THA significantly reduced perioperative blood loss. Therefore, bone wax is promising for optimising blood-conserving management protocols in THA.